KAJIAN EFEKTIVITAS MANAJEMEN SUMBER DAYA MANUSIA DI COUNTRY CLUB GOLF GRAHA FAMILI SURABAYA - Gemilang, Dedi Surya; ASHADI, KUNJUNG (Arena, 2014)
Effectiveness is the extent to which organizations carry out the entire task or achieve substantially all of the target. The effectiveness of the theory viewed from 1) the purpose of the company, 2) achievement run basic tasks are reflected in the General Standard of Operations and Procedures. The purpose of this research is to find out how the effectiveness of human resource management at the Country Club Golf Graha Famili seen from two aspects. It can be concluded that, the level of effectiveness in the Country Club Golf Graha Famili very good. Goals and Objectives achieved the desired company can be seen from the assessment of the suitability of a member who expresses the percentage up to 81%. It can be realized because of absence of control by managers based checklist that exist in every part. And provide reward and punishment in accordance with company regulations.